2014
DOI: 10.1364/ome.4.001166
|View full text |Cite
|
Sign up to set email alerts
|

Optical ridge waveguides in 4H-SiC single crystal produced by combination of carbon ion irradiation and femtosecond laser ablation

Abstract: Optical ridge waveguides were fabricated in 4H-SiC single crystal by combination of 15 MeV C 5+ ion irradiation and femtosecond laser ablation. The near-field modal intensity distributions exhibit the wellconfined light propagation in the waveguides. A propagation loss as low as 5.1 dB/cm has been achieved at 632.8 nm for the ridge waveguide. The investigation of confocal micro-Raman spectra suggests partial transition of 4H-SiC to 6H-SiC in the irradiated region.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…To construct 2D ridge waveguides, swift heavy ion irradiation or ion implantation must be combined with other technique, such as wet or dry etching [17], diamond blade dicing [18], and laser ablation, to remove certain parts of the planar waveguides in order to achieve refractive index contrast along the horizontal direction for light field confinement. The combination of laser ablation and swift heavy ion irradiation has been implemented in several materials to manufacture ridges with high quality [19,20]. As for upconversion emission in waveguide, Liu et al have reported on the green upconversion pumped by 800-nm laser in planar waveguide based on Er 3+ /MgO codoped LiNbO 3 crystal [21].…”
Section: Introductionmentioning
confidence: 99%
“…To construct 2D ridge waveguides, swift heavy ion irradiation or ion implantation must be combined with other technique, such as wet or dry etching [17], diamond blade dicing [18], and laser ablation, to remove certain parts of the planar waveguides in order to achieve refractive index contrast along the horizontal direction for light field confinement. The combination of laser ablation and swift heavy ion irradiation has been implemented in several materials to manufacture ridges with high quality [19,20]. As for upconversion emission in waveguide, Liu et al have reported on the green upconversion pumped by 800-nm laser in planar waveguide based on Er 3+ /MgO codoped LiNbO 3 crystal [21].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, femtosecond pulsed laser ablation is superior when ablating ultrahard and hard-to-etch materials such as SiC. So far, the femtosecond laser micromachining technique has shown success in ablating SiC films on Si substrates for MEMS devices [27], optical ridge waveguide formation [28], in-air throughhole fabrication in SiC substrates [29], and alcohol-assisted through-hole drilling in SiC [30]. However, the SiC MEMS devices fabricated by femtosecond laser micromachining were restricted to the surface thin film and the SiC throughwafer studies were focused merely on the characterization of the via holes by single shot ablation.…”
Section: Journal Of Micromechanics and Microengineeringmentioning
confidence: 99%
“…Nevertheless, it causes the modification of the surface refractive index and a change in the material phase structure when the femtosecond laser irradiates the sample. By controlling the specific parameters of femtosecond laser irradiation, self-assembled periodic nanostructures [23] and SiC optical waveguides [24,25] induced by femtosecond laser irradiation were observed. With the increase in laser fluence, the irradiated sample is melted and reshaped by laser ablation, forming micro-cracks and holes.…”
Section: Introductionmentioning
confidence: 99%